Communication Styles among Malaysian Graduate Students - Wong, Ko Chai (2002)
The communication styles of Malay, Chinese and Indian adults have not been thoroughly investigated and are, therefore, not we11 understood. The purpose of this study is to identify the communication styles of Malay, Chinese and Indian adults, and the relationship of self-construal and demography factors with communication style. A sample of 256 graduate students at UPM participated in the survey using nonrandom quota sampling. A self-administered questionnaire was used as a research instrument, and a drop and pick-up method was used to collect the relevant data. The statistical techniques used to analyze the data were descriptive statistics, t-test, one-way ANOVA and MANCOVA. The findings of this study suggest that a friendly style is predominant among the Malay adults, an attentive style is more predominant among the Chinese adults, and, friendly and animated styles are marked among the Indian adults. The results showed that self-construal is a good predictor of communication styles with independent self-construal a better predictor of communication styles than interdependent self-construal. The results also showed that age, gender and religion are poor predictors of communication styles.